Ionic conductivity of PVdF-co-HFP/LiClO4 in terms of free volume defects probed by positron annihilation lifetime spectroscopy. Issue 3 (3rd April 2019) - Yahsi, Ugur; Deligöz, Hüseyin; Tav, Cumali; Ulutaş, Kemal; Değer, Deniz; Yılmaztürk, Serpil; Erdemci, Gonca; Coşkun, Bilgehan; Yılmazoğlu, Mesut; Yakut, Şahin
ABSTRACT: Polymers based on ionic conducting materials have important interest because of their potential applications in polymer electrolytes and membranes for fuel cell application. PVdF-co-HFP poly(viniliden-co-hexafluoropropylene) was chosen as a polymer matrix because of its high ionic conductivity and better mechanical properties. Polymer matrix composites were prepared with various amounts of LiClO4 salt by a solution casting method. The sample-ionic conductivity measurements were recorded by AC impedance analyzer at different frequencies from 0.1 Hz to 20 MHz and at different temperatures from 273 to 373 K. The changes of nanoscopic free volume and free volume fraction in these materials were investigated in terms of temperature from 273 to 373 K using Positron Annihilation Lifetime Spectroscopy (PALS) and Simha-Somcynsky (SS) Hole Theory. The free volume had a bump at about 3% in weight percentage of the salt and there is a slight increase after 10%. The effects of weight percentages of LiClO4 and temperature were investigated. The mechanism of the ac ionic conductivity was presented in terms of the free volume models, however thermo-occupancy function justifies the best accurate representation of the data.